2015
DOI: 10.1093/gbe/evv075
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Gene Expression after Gene Amplification

Abstract: We took a rather unique approach to investigate the conservation of gene expression of prolamin storage protein genes across two different subfamilies of the Poaceae. We took advantage of oat plants carrying single maize chromosomes in different cultivars, called oat–maize addition (OMA) lines, which permitted us to determine whether regulation of gene expression was conserved between the two species. We found that γ-zeins are expressed in OMA7.06, which carries maize chromosome 7 even in the absence of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“… b The percentages of different prolamin species in total prolamins were from a previous study ( Ogawa et al 1987 ). c The percentage of different types of teff prolamins in total prolamins was calculated by protein band densitometry from Image J, following a previous protocol ( Garcia et al 2015 ). d Percentages of different zeins in total maize prolamins were from previous reports ( Thompson and Larkins 1994 ; Wu et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… b The percentages of different prolamin species in total prolamins were from a previous study ( Ogawa et al 1987 ). c The percentage of different types of teff prolamins in total prolamins was calculated by protein band densitometry from Image J, following a previous protocol ( Garcia et al 2015 ). d Percentages of different zeins in total maize prolamins were from previous reports ( Thompson and Larkins 1994 ; Wu et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“… c The percentage of different types of teff prolamins in total prolamins was calculated by protein band densitometry from Image J, following a previous protocol ( Garcia et al 2015 ). …”
Section: Discussionmentioning
confidence: 99%
“…S4B). Indeed, its regulator, the transcription factor Prolamin box binding factor 1 (Pbf1), whose function is conserved across cereals (15), is also reduced in the dek seeds (Fig. S4C).…”
Section: Significancementioning
confidence: 99%
“…The OMA lines were used in the cytogenetic mapping system for maize genome ( Riera-Lizarazu, Rines & Phillips, 1996 ; Maquieira, 1997 ; Kynast et al, 2001 ; Kynast et al, 2002 ; Okagaki et al, 2001 ; Koumbaris & Bass, 2003 ), gene expression ( Jin et al, 2004 ), meiotic chromosome arrangements ( Bass et al, 2000 ), investigation of conservation of gene expression of prolamin storage protein ( Garcia et al, 2015 ) as well as investigation of genes transcriptional regulation in new genomic environments ( Dong et al, 2018 ). It was shown that the majority of maize genes displayed maize-specific transcription in the oat genomic environment.…”
Section: Introductionmentioning
confidence: 99%